Application of LCA modelling in integrated waste management. (December 2020) - Christensen, T.H.; Damgaard, A.; Levis, J.; Zhao, Y.; Björklund, A.; Arena, U.; Barlaz, M.A.; Starostina, V.; Boldrin, A.; Astrup, T.F.; Bisinella, V.
Highlights: LCA provides a much improved holistic view of waste management. LCA helps understanding waste flows and potential environmental impacts. There is still a need to use LCA models in integrated waste management. LCA is expected to play a role in six areas of waste management in the future. Abstract: Life cycle assessment (LCA) has been used in waste management for the last two decades and hundreds of journal papers have been published. The use of LCA in waste management has provided a much-improved holistic view of waste management including waste flows and potential environmental impacts. Although much knowledge has been obtained from LCA studies, there is still a need to use LCA models in integrated waste management. This paper describes six areas where LCA is expected to play a role in waste management in the future: 1) understanding an existing waste management system; 2) improving existing waste management systems; 3) comparing alternative technologies/ technology performance; 4) technology development/prospective technologies; 5) policy development/strategic development; and 6) reporting. Illustrative examples are provided for each application area.